Molybdenum-containing powder

CN118103158BActive Publication Date: 2026-10-27A L M T CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280068397.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-13
Filing Date
2022-10-06
Publication Date
2026-10-27
Estimated Expiration
2042-10-06

Smart Images

  • Figure BDA0004784169220000091
    Figure BDA0004784169220000091
  • Figure BDA0004784169220000101
    Figure BDA0004784169220000101
Patent Text Reader

Abstract

A molybdenum-containing powder having an average particle diameter of 0.5 μm or more and 3.0 μm or less based on the Fsss method, a BET specific surface area of 0.3 m 2 / g or more and 5.5 m 2 / g or less, a coagulation factor calculated from the average particle diameter based on the Fsss method and the BET specific surface area based on the gas adsorption method of 5.5 or less, and an apparent density of 2.13 g / cm 3 or less, according to JIS Z 2504 (2012).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to molybdenum-containing powders. This application claims priority based on Japanese Patent Application No. 2021-168283, filed on October 13, 2021. The entire contents of that Japanese patent application are incorporated herein by reference. Background Technology

[0002] Previously, molybdenum-containing powders were disclosed, for example, in Japanese Patent Application Publication No. 11-36006 (Patent Document 1).

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 11-36006 Summary of the Invention

[0006] The molybdenum-containing powder disclosed herein has an average particle size of 0.5 μm to 3.0 μm based on the FSSS method, and a BET specific surface area of ​​0.3 m² based on the gas adsorption method. 2 / g or more 5.5m 2 The particle size is below 5.5 g / cm³, and the aggregation coefficient calculated based on the average particle size and BET specific surface area using the FSSS method is below 5.5. The apparent density, measured according to JIS Z 2504 (2012), is 2.13 g / cm³. 3 the following. Detailed Implementation

[0007] [The problem this disclosure aims to solve]

[0008] Previously, molybdenum-containing powders had problems such as poor sintering properties.

[0009] [Description of embodiments of this disclosure]

[0010] First, embodiments of this disclosure will be listed and described.

[0011] In conventional methods, ammonium molybdate or MoO3 (molybdenum trioxide) powder is filled into a reduction vessel (e.g., a heat-resistant alloy vessel), inserted into a reduction furnace in a hydrogen atmosphere, and reduced at a certain temperature to produce an intermediate product. This intermediate product is then further heated at a high temperature to produce Mo powder. A characteristic of molybdenum powder produced by this method is that, in order to obtain a dense molybdenum sintered body using conventional powder metallurgy, a sintering temperature of approximately 1800°C to 2000°C is required; high-temperature sintering is necessary. This is the reason for the high sintering cost of molybdenum-containing powder produced by conventional methods.

[0012] Furthermore, in the bonding of materials such as metallization and ceramics (excluding molybdenum), the sintering (bonding) temperature with materials containing molybdenum powder is typically above 1000°C. This can sometimes lead to problems such as warping in the sintered workpiece due to the difference in thermal expansion between the molybdenum powder and the ceramic material. The primary cause is believed to be the shrinkage characteristics during sintering resulting from variations in the particle size of the molybdenum powder and particle agglomeration.

[0013] In conventional powder metallurgy methods for manufacturing molybdenum-containing powders, agglomeration is prone to occur. To obtain finely sinterable molybdenum powder using existing methods, reduction is required at lower temperatures, which hinders particle growth and tends to result in greater agglomeration. A trade-off exists between reducing particle size to improve sinterability and the degree of agglomeration in the resulting finely sintered molybdenum powder.

[0014] Considering these factors, molybdenum powder with properties such as fine particles, low agglomeration, and good sinterability at low temperatures is considered useful.

[0015] In the powder metallurgy method of Patent Document 1, K and P are doped into the intermediate product generated during the reduction of ammonium molybdate or MoO3 (molybdenum trioxide) powder, and then reduced in a hydrogen atmosphere. A method for manufacturing molybdenum powder with an apparent density of 2.2 or higher and without uniform particles smaller than 22 μm in the particle size distribution is described. It is believed that, compared to conventional molybdenum-containing powders, the Mo powder produced by the method of Patent Document 1 exhibits less agglomeration but larger particle size, resulting in poor sintering properties. Furthermore, Patent Document 1 describes an increase in the filling density of Mo powder but makes no mention of sintering properties.

[0016] The molybdenum-containing powder disclosed herein has an average particle size (hereinafter also referred to as FSSS average particle size) of 0.5 μm to 3.0 μm based on the FSSS method, and a BET specific surface area (hereinafter also referred to as BET specific surface area) of 0.3 μm based on the gas adsorption method. 2 / g or more 5.5m 2 The agglomeration coefficient calculated from the average particle size and BET specific surface area based on the Fsss method is below 5.5.

[0017] (1) Description of objects

[0018] This disclosure relates to molybdenum-containing powders with low agglomeration and excellent sinterability, and it has been found that the following characteristic values ​​can be set within a predetermined range to achieve the desired effect.

[0019] Regarding the FSSs average particle size, BET specific surface area, and aggregation coefficient, the necessary ranges are: FSSs average particle size between 0.5 μm and 3.0 μm, and BET specific surface area between 0.3 μm and 3.0 μm. 2 / g or more 5.5m 2For g, the cohesion coefficient is below 5.5. The cohesion coefficient γ is expressed by the following formula.

[0020] γ = Fsss average particle size / d = (Fsss average particle size × BET specific surface area × ρ) / 6

[0021] Here, d is the BET particle size calculated from the BET specific surface area, and ρ is the density.

[0022] A more preferred range is: an average Fsss particle size of 0.5 μm to 3.0 μm and a BET specific surface area of ​​0.3 m². 2 / g or more 5.5m 2 / g or less, and the cohesion coefficient is between 1.5 and 5.1.

[0023] A further preferred range is: an average Fsss particle size of 0.5 μm to 2.5 μm and a BET specific surface area of ​​0.4 m². 2 / g or more 5.5m 2 The cohesion coefficient is between 1.5 and 5.1 for g / g or less. If it falls within this range, the sinterability is further improved.

[0024] The preferred range for molybdenum purity is 99.5% by mass or higher. A more preferred range is 99.9% by mass or higher. Within this range, impurities are less likely to affect sinterability.

[0025] Other than molybdenum, the composition may contain at least one of the following: Al, Ca, Cr, Cu, Fe, Mg, Mn, Ni, Pb, Sn, Si, Na, K, As, P, and W. The proportion of each component is less than 0.1% by mass. For analytical methods, Fe, Ca, Si, Al, and Mg can be analyzed using JISH1404 (2001); K, Na, and As can be analyzed using atomic absorption spectrometry (Analytic Quantum Japan: control AA300); and P and other metals can be analyzed using ICP emission spectrometry (Shimadzu Corporation: ICPS-8100).

[0026] The preferred range for particle size distribution is D90 / D10 of 4.3 or less. A more preferred range is D90 / D10 of 1.5 or more but less than 4.0. Within this range, sinterability is further improved.

[0027] D90 represents the D90% diameter, which refers to the particle size in the particle size distribution diagram where the cumulative frequency of particles below this diameter is 90%. D10 represents the D10% diameter, which refers to the particle size in the particle size distribution diagram where the cumulative frequency of particles below this diameter is 10%. If within this range, the sinterability is further improved.

[0028] The preferred range for crystallite size is below 1000 nm. A more preferred range is crystallite size between 75 nm and 980 nm. Within this range, sinterability is further improved.

[0029] The preferred range for lattice distortion is 0.018% or more. A more preferred range is 0.02% or more. Within this range, sinterability is further improved.

[0030] As a result, a relative density of over 70% can be achieved when sintering at 800℃, and a relative density of over 85% can be achieved when sintering at 1400℃.

[0031] The apparent density, as determined by JIS Z 2504 (2012), is 2.13 g / cm³. 3 Preferably, the tap density, as determined by JIS Z 2512 (2012), is 4.34 g / cm³. 3 the following.

[0032] (2) Manufacturing method

[0033] The process involves manufacturing molybdenum-containing powder through steps 1 (raw material screening), 2 (first-stage reduction), 3 (intermediate screening), 4 (second-stage reduction), 5 (final screening), and 6 (grinding in a mortar).

[0034] Process 1: Raw material screening

[0035] The MoO3 powder used as raw material is sieved. The raw material is passed through a sieve with a predetermined mesh size to remove coarse particles and agglomerated powder, and the undersize material is recovered. The mesh size of the sieve is appropriately adjusted according to the raw material and the particle size of the target molybdenum powder.

[0036] Step 2: Single-stage reduction (MoO3→MoO2)

[0037] The sieved MoO3 from step 1 is filled into a heat-resistant alloy boat to reduce the MoO3 to MoO2, which is then removed. Optimal reduction conditions (temperature, hydrogen flow rate, boat filling amount, equipment used, etc.) are selected appropriately based on the particle size of the target powder.

[0038] Step 3: Intermediate screening

[0039] The MoO2 powder obtained in step 2 is sieved. The MoO2 powder is passed through a sieve with a predetermined mesh size to remove coarse particles and agglomerated powder, and the undersize material is recovered. The mesh size of the sieve is appropriately adjusted according to the particle size of the MoO2 powder and the target molybdenum powder.

[0040] Step 4: Two-stage reduction (MoO2→Mo)

[0041] The sieved MoO2 from step 3 is filled into a heat-resistant alloy boat to reduce it to Mo, which is then removed. Optimal reduction conditions (temperature, hydrogen flow rate, boat filling amount, equipment used, etc.) are selected based on the particle size of the target powder. This yields a molybdenum-containing powder.

[0042] Step 5: Final screening

[0043] The molybdenum-containing powder obtained in step 4 is sieved. The molybdenum-containing powder is passed through a sieve with a predetermined mesh size to remove coarse particles and agglomerated powder, and the undersize is recovered. The mesh size of the sieve is appropriately adjusted according to the particle size of the molybdenum-containing powder and the target molybdenum powder.

[0044] Step 6: Grinding in a mortar and pestle

[0045] The molybdenum-containing powder obtained in step 5 is rubbed in a mortar. This introduces lattice distortion while simultaneously pulverizing the remaining agglomerated powder.

[0046] [Details of the embodiments disclosed herein]

[0047] <Example>

[0048] Manufacturing of Sample No. 1

[0049] The process involves manufacturing molybdenum-containing powder through steps 1 (raw material screening), 2 (first-stage reduction), 3 (intermediate screening), 4 (second-stage reduction), 5 (final screening), and 6 (grinding in a mortar).

[0050] Process 1: Raw material screening

[0051] The raw material used is MoO3 powder with an average particle size of 4 μm and a molybdenum purity of ≥66.33% (equivalent to ≥99.5% when converted to Mo powder). The powder is sieved using a 250 μm mesh to remove coarse particles and agglomerated powder, and the undersize material is recovered.

[0052] The preferred average particle size of the FeSSS is 0.5 μm to 50 μm. When this value is exceeded, the average FeSSS particle size of the molybdenum-containing powder may become 3.0 μm or larger. It should be noted that "may" means there is a slight possibility that it will become that way, not that it has a high probability of becoming that way.

[0053] The molybdenum purity in MoO3 is preferably above 66.33% (equivalent to above 99.5% when converted to Mo powder).

[0054] When the purity is less than this value, it may become low-purity and unsuitable for industrial products.

[0055] It should be noted that the purity of molybdenum in MoO3 is preferably above 66.6% (equivalent to above 99.9% when converted to Mo powder). This is because the more impurities contained in molybdenum, the more likely it is to affect the sinterability of molybdenum.

[0056] The mesh size is preferably below 300 μm. If it exceeds this value, it may be impossible to remove coarse particles or agglomerated powder.

[0057] Step 2: Single-stage reduction (MoO3→MoO2)

[0058] The MoO3 sieved in step 1 was filled into a heat-resistant alloy boat to a thickness of 35 mm. A push-type reduction furnace was used with a hydrogen flow rate of 5 m³ / h. 3 MoO2 was obtained by reduction treatment at a reduction temperature of 500℃ and a reduction rate of 0.06 h.

[0059] The thickness of MoO3 filled in the alloy boat is preferably less than 50 mm. When this value is exceeded, the reduction of MoO3 in the boat may not be possible.

[0060] The preferred hydrogen flow rate is 3m. 3 / h or higher. When the value is less than this, the reduction of MoO3 in the boat may not be possible.

[0061] The reduction temperature is preferably between 450°C and 650°C. When this temperature exceeds this value, the MoO3 raw material may melt due to proximity to its melting point. When this temperature is below this value, the reduction of MoO3 in the boat may not be possible.

[0062] Step 3: Intermediate screening

[0063] The MoO2 obtained in step 2 is sieved using a 75μm mesh to remove coarse particles and agglomerated powder, and the screened material is recovered.

[0064] The mesh size is preferably below 150 μm. If it exceeds this value, it may be impossible to remove coarse particles or agglomerated powder.

[0065] Step 4: Two-stage reduction (reduction of MoO2)

[0066] The MoO2 obtained from the intermediate sieving in step 3 was filled into a heat-resistant alloy boat to a thickness of 20 mm. A push-type reduction furnace was used with a hydrogen flow rate of 10 m³ / h. 3 The reduction process is carried out under conditions of approximately 600–920°C per hour and a reduction temperature of approximately 600–920°C to obtain molybdenum-containing powder.

[0067] The thickness of MoO2 filled in the heat-resistant alloy boat is preferably less than 50 mm. When this value is exceeded, the reduction of MoO2 in the boat may not be possible.

[0068] The preferred hydrogen flow rate is 5m.3 / h or higher. When the value is less than this, the reduction of MoO2 in the boat may not be possible.

[0069] The reduction temperature is preferably between 600°C and 950°C. When this value is exceeded, the average particle size (Fsss) of the molybdenum-containing powder may become greater than 3.0 μm. When this value is lower, the reduction of MoO2 in the boat may not be possible.

[0070] Step 5: Final Screening

[0071] The obtained molybdenum-containing powder was sieved using a mesh size of less than 45 μm (20 μm in sample number 1) to remove coarse particles and agglomerated powder, and the undersize material was recovered.

[0072] The mesh size is preferably below 45 μm. If it exceeds this value, it may be impossible to remove coarse particles or agglomerated powder.

[0073] Step 6: Grinding in a mortar and pestle

[0074] The Mo powder obtained from the final sieving is pulverized using an automatic mortar and pestle. 500g is added per batch and pounded for 10 minutes.

[0075] For samples 2 to 33, the reduction conditions (temperature, hydrogen flow rate, and boat filling amount) in the two-stage reduction process of step 4 and the mesh size of the sieve in the final sieving process of step 5 are changed based on the manufacturing method of sample 1.

[0076] For the comparative samples 41 to 60, the reduction conditions (temperature, hydrogen flow rate, and boat filling amount) in step 4 (two-stage reduction) and the mesh size of the sieve in step 5 (final sieving) were changed, and step 6 (grinding in a mortar) was omitted. This resulted in molybdenum-containing powders for samples 1 to 33 and 41 to 60.

[0077] The molybdenum-containing powder was evaluated as follows.

[0078] <Method for determining the average particle size of Fsss>

[0079] The average particle size of Fsss was determined by the Fischer method.

[0080] The apparatus used was a Fisher Sub-Sieve Sizer Model 95 from Fisher Scientific. A sample of true density was filled into the sample tube, and the porosity was calculated based on the sample height. Air at a pressure of 1 MPa was passed through the sample tube, and the manometer water level was read from the calculator chart. This value was taken as the Fsss average particle size, expressed in μm. The Fsss average particle size represents the average particle size of the powder; a lower value indicates a smaller average particle size.

[0081] <BET specific surface area>

[0082] The BET specific surface area was determined by gas adsorption. The apparatus used was a Macsorb HM Model-1208 from MOUNTECH. Nitrogen gas was adsorbed onto the powder, and the BET specific surface area of ​​the powder was determined based on the amount of adsorbed gas molecules. The unit of BET specific surface area is m². 2 / g indicates that the smaller the average particle size of Fsss, the larger the BET specific surface area tends to be.

[0083] <Cohesion Coefficient>

[0084] The cohesion coefficient is expressed as the ratio of the Fsss average particle size (μm) to the BET particle size (μm) calculated from the BET specific surface area. A cohesion coefficient closer to 1 indicates less cohesion, while a larger coefficient indicates more cohesion. In principle, the cohesion coefficient should be ≥1.

[0085] The Fsss average particle size refers to the secondary particle size including agglomerates, while the BET particle size calculated from the BET specific surface area refers to the value close to the primary particle size without agglomerates.

[0086] Assuming the particles are spherical, the BET specific surface area (m²) 3 The following formula holds true between ρ (g / cm³) and BET particle size (diameter) d (μm). Where ρ represents density (g / cm³). 3 ).

[0087] BET specific surface area = 6 / ρd

[0088] That is, the BET particle size d is d = 6 / (ρ × BET specific surface area).

[0089] Therefore, the cohesion coefficient γ is γ = Fsss average particle size / d = (Fsss average particle size × BET specific surface area × ρ) / 6.

[0090] <Methods for determining particle size distribution>

[0091] Particle size distribution was determined by laser diffraction / scattering. D90 and D10 were then calculated.

[0092] The apparatus used was a Microtrac MRB MT3300EX2 laser diffraction / scattering type. Pure water was used as the solvent; the particle refractive index was 2.76, and the solvent refractive index was 1.33.

[0093] The larger the D90 / D10 value, the wider the particle size distribution; conversely, the smaller the value, the sharper the particle size distribution (uniform particle size).

[0094] <Lattice distortion, crystallite size>

[0095] Lattice distortion and crystallite size were determined by X-ray diffraction.

[0096] The apparatus used is the EMPYREAM from PANalytical. When X-rays of a certain wavelength are irradiated onto the sample to be analyzed, the scattered X-rays display a unique diffraction pattern based on the arrangement of the atoms / molecules of the material. Rietveld analysis, which uses nonlinear least squares fitting, is performed based on this diffraction pattern to determine the lattice distortion and crystallite size.

[0097] Crystallite size refers to the smallest unit in a grain that can be considered a single crystal. When the crystallite size is small, the grain size tends to be smaller. When the grain size is small, the contact area between the grains becomes larger, making sintering easier and thus increasing the relative density of the sintered body.

[0098] When matter is observed at the atomic level, atoms are arranged in a lattice. When a force is applied to this lattice, its shape changes, resulting in deformation. This deformation is called lattice distortion.

[0099] <Apparent density, tap density>

[0100] The analytical method for apparent density is JIS Z2504 (2012), and the analytical method for tap density is JIS Z2512 (2012). When the determination method in Patent Document 1, i.e., the determination method of Tungsten / Molybdenum Industry Association Standard TMS1101, is compared with the determination method of the above-mentioned JIS, the determination results are roughly the same.

[0101] These results are shown in Tables 1 and 2.

[0102] [Table 1]

[0103]

[0104] [Table 2]

[0105]

[0106] In Tables 1 and 2, "final sieving mesh" refers to the mesh size of the sieve used in the final sieving of step 5. "Grinding in mortar" indicates whether grinding in mortar is performed in step 6. "Fsss", "BET", "agglomeration coefficient", "particle size distribution", and "crystal size" refer to the average particle size (Fsss), specific surface area (BET), agglomeration coefficient, particle size distribution (D90 / D10), and crystallite size of the molybdenum-containing powder obtained through step 5 or 6.

[0107] Sintered bodies were prepared using the molybdenum-containing powders shown in Tables 1 and 2, and their densities were determined. The method for determining the density of sintered bodies is described below.

[0108] For the preparation of the sintered body used for density determination, 10g of molybdenum-containing powder was first placed in a φ20mm mold and pressed into shape using a 30t press with a pressure of 50MPa. Then, it was sintered in a hydrogen atmosphere at 800℃ for 2 hours, or at 1400℃ for 2 hours, to obtain the sintered body. Paraffin wax was then impregnated into the sintered body for about 10 minutes to fill the voids, and the density of the sintered body was then determined using the Archimedes method.

[0109] These results are shown in Tables 3 and 4.

[0110] [Table 3]

[0111] 1 80.6 95.3 2 81.2 96.2 3 81.4 96.3 4 79.5 95.3 5 79.3 95.1 6 78.1 94.0 7 77.7 93.6 8 75.2 91.6 9 77.2 93.1 10 75.7 92.0 11 74.4 91.4 12 76.2 93.1 13 76.1 92.5 14 75.5 91.1 15 75.3 90.7 16 75.8 91.0 17 73.5 88.9 18 73.1 88.8 19 74.9 89.9 20 74.1 89.1 21 73.9 88.9 22 72.1 87.6 23 73.8 88.6 24 71.5 87.0 25 73.4 88.0 26 72.6 87.4 27 72.5 87.3 28 70.9 85.8 29 72.6 87.5 30 71.4 86.3 31 70.4 85.1 32 70.2 85.0 33 71.0 85.9

[0112] [Table 4]

[0113] 41 69.3 84.8 42 68.8 84.3 43 69.7 84.2 44 68.7 84.3 45 69.8 84.5 46 69.4 84.2 47 68.9 83.9 48 69.1 84.0 49 68.5 83.9 50 68.2 83.7 51 68.0 83.4 52 67.4 83.1 53 67.1 82.4 54 67.0 82.1 55 66.5 81.1 56 64.2 79.4 57 64.1 79.0 58 63.4 78.5 59 62.2 77.4 60 61.1 76.1

[0114] The "relative density after sintering at 800℃" in Tables 3 and 4 refers to the relative density of the sintered body after sintering at 800℃. The "relative density after sintering at 1400℃" refers to the relative density of the sintered body after sintering at 1400℃.

[0115] When sintering at a temperature of 800℃, a relative density of 70% or higher is considered to indicate good sinterability. When sintering at a temperature of 1400℃, a relative density of 85% or higher is considered to indicate good sinterability.

[0116] It can be seen that among samples numbered 1 to 33, there is less agglomeration, the particles are microparticles / uniform particles, and there is more lattice distortion. Therefore, these are molybdenum-containing powders that are easier to sinter at low temperatures compared to previous samples. As a result, the sintering cost becomes cheaper, and the energy used is also reduced, thus solving the energy problem.

[0117] Because it can be sintered at low temperatures, it has a small difference in thermal expansion compared to other materials, making it easy to sinter. Therefore, when used for metallization applications, the shrinkage rate can be controlled by the sintering temperature.

[0118] Sintered bodies capable of plastic processing such as rolling or forging require a relative density of 85% or higher. To manufacture such sintered bodies, molybdenum shaped bodies need to be sintered at temperatures above 1800°C. However, the present invention can be manufactured at a temperature of 1400°C, thus reducing manufacturing costs.

[0119] It can be seen that among the samples 4, 10, 18, and 28 with a cohesion coefficient exceeding 5.1, the sinterability is slightly lower compared to the samples in Tables 1 and 3, which have the same Fsss average particle size or BET specific surface area. Therefore, a cohesion coefficient of 1.5 or higher and 5.1 or lower is more preferable.

[0120] In addition, according to the results in Tables 1 and 3, the smaller the average particle size of Fsss, the higher the relative density after sintering at 800℃ and 1400℃ tends to be, and the larger the BET specific surface area tends to be.

[0121] In samples 28, 29, 30, 31, 32, and 33 with an average Fsss particle size exceeding 2.5 μm, the relative densities after sintering at 800 °C and 1400 °C were close to the lower limits of 70% and 85% or more, respectively, which are considered effective according to this disclosure. Furthermore, in samples 30 and 33 with an average Fsss particle size of 2.5 μm and a BET specific surface area less than 0.5, compared to samples 27 and 29, the relative densities after sintering at 800 °C were less than 72% and less than 85% respectively, indicating reduced sinterability. Therefore, the average Fsss particle size is further preferably 0.5 μm to 2.5 μm, and the BET specific surface area is further preferably 0.4 μm. 2 / g or more 5.5m 2 The cohesion coefficient is further preferably 1.5 or higher and 5.1 or lower than / g.

[0122] It can be seen that among the samples 8, 18, and 28 with a particle size distribution D90 / D10 exceeding 4.3, the sinterability is slightly lower compared to the samples in Tables 1 and 3, which have the same Fsss average particle size or BET specific surface area. Therefore, the particle size distribution D90 / D10 is preferably 4.3 or less.

[0123] Furthermore, it is known that among samples 11, 17, 19, and 24 with a particle size distribution D90 / D10 exceeding 4.0, the sinterability is slightly reduced compared to samples in Tables 1 and 3, which have equivalent Fsss average particle size or BET specific surface area. Therefore, a particle size distribution D90 / D10 of 4.3 or less is more preferable.

[0124] It can be seen that among samples 31 and 32 with crystallite sizes exceeding 1000 nm, the sinterability is slightly reduced compared to samples in Tables 1 and 3, which have the same Fsss average particle size or BET specific surface area. Therefore, the crystallite size is preferably below 1000 nm.

[0125] Furthermore, it is known that sample number 33, with a crystallite size exceeding 980 nm, exhibits slightly lower sinterability compared to samples in Tables 1 and 3, which have the same Fsss average particle size or BET specific surface area. Therefore, a crystallite size of 75 nm to 980 nm is more preferable.

[0126] Furthermore, it is known that for samples 11, 17, 22, 24, and 32 with lattice distortion less than 0.018%, the sinterability is slightly lower compared to samples 1 and 3 in Table 1, which have the same Fsss average particle size or BET specific surface area. Therefore, the lattice distortion is preferably 0.018% or higher.

[0127] Furthermore, it is known that for samples 18, 28, and 31 with lattice distortion less than 0.020%, the sinterability is slightly lower compared to samples in Tables 1 and 3, which have the same Fsss average particle size or BET specific surface area. Therefore, lattice distortion is preferably 0.020% or higher.

[0128] According to Tables 1 and 2, the apparent density, as determined by JIS Z 2504 (2012), is less than 1.96 g / cm³. 3 The preferred tap density, determined according to JIS Z 2512 (2012), is 4.34 g / cm³. 3 the following.

[0129] It should be considered that the embodiments and examples disclosed herein are exemplary and not restrictive in all respects. The scope of the invention is defined by the claims rather than the foregoing description and is intended to include all modifications within the meaning and scope equivalent to the claims.

Claims

1. A molybdenum-containing powder, having an average particle size of 0.5 μm to 3.0 μm based on the FSSS method, and a BET specific surface area of ​​0.3 m² based on gas adsorption. 2 / g or more 5.5m 2 For particles with a particle size below 5.5 g / cm³, the aggregation coefficient calculated using the following formula based on the average particle size obtained by the FSSS method and the BET specific surface area obtained by the gas adsorption method is below 5.5, and the apparent density measured according to JIS Z 2504:2012 is 2.13 g / cm³. 3 The following values ​​assume that the ratio D90 / D10 is 4.3 or less when the D10% diameter and D90% diameter of the particle size distribution are set to D10 and D90, respectively. Cohesion coefficient = (Fsss average particle size × BET specific surface area × ρ) / 6 ρ is density, with units of g / cm³. 3 .

2. The molybdenum-containing powder according to claim 1, wherein, The molybdenum purity is above 99.5% by mass, with the balance consisting only of unavoidable impurities.

3. The molybdenum-containing powder according to claim 1 or 2, wherein, The crystallite size is below 1000nm.

4. The molybdenum-containing powder according to claim 1 or 2, wherein, The lattice distortion is greater than 0.018%.

5. The molybdenum-containing powder according to claim 1 or 2, wherein, The tap density, as determined by JIS Z 2512:2012, is 4.34 g / cm³. 3 the following.

Citation Information

Patent Citations

  • Uniformly grained molybdenum powder and its production

    JP1999036006A

  • Electromagnetic relay and electronic circuit

    JP2021168283A

  • Production of molybdenum metal powder

    CN102369075A

  • Mo-Cu composite powder

    CN1326833A